Harnessing photoinduced electron transfer to optically determine protein sub-nanoscale atomic distances - Antonios Pantazis (Nature Portfolio, 2018)
Current Förster resonance energy transfer (FRET)-based fluorescence spectroscopy methods are suffering from some limitations in the field of structural biology. Here, the authors present an optical approach, distance-encoding photoinduced electron transfer (DEPET), capable of the simultaneous study of protein structure and function.